The Pulpits of Mosul Mosques During the Era of the Central Administration (1250-1337 A.H / 1834-1918 A.D) - وسن عبد المطلب حسن م. (lark, 2021)
The subject of research is an integrated membership unit for the pulpits that studied.As it is considered an important crucial aspect in the study of Islamic monuments which did not receive enough attention, and this reflecting how important they are in highlighting traces that have been deliberately removed or they change during the wrong maintenance and that’s lost its beauty, as in the case in all of the mosque of "Al_Nabi Jergees" that destroyed by terrorist, and Sheikh Mohamed mosque that part of it were damaged when it happened in its original pulpits, when they removed it and rebuilt it in a different way to what it was. Likewise, the pulpits of the Imam Baher, Al_Jwijati and Baker Effendi mosques, all of them were subjected to change when rebuilt in a wrong way, as the beauty of the pulpit was lost. The aim of the research was to continue building these pulpits historically, noting that the study depends on the plans and pictures that we have been attached by us, which make the path clear to archaeologists, and allow them to determine the history of these pulpits in relying on scientific facts. For our field visits before they are vandalized and destroyed, to study them and complete its studies of the pulpits previously.